Development of a Real-Time Web-Based Battalion Picket Activity Monitoring System: A Case Study of the INFO GIAT Application - Wibowo, Satrio; Yuliandhita Puspita Maharani, Alya; Richard Arieadhie, Mochammad; Maulana, M. Yusuf; Ahmad Firdaus, Eryan (Marqcha Institute, 2026)
Operational effectiveness in a Battalion environment depends heavily on the discipline and orderly execution of picket duties. However, reliance on manual administration such as physical journals and fragmented data recapitulation creates bottlenecks in the flow of vital information, increases the risk of data loss, and limits leadership’s ability to supervise unit activities in real-time. This research develops INFO GIAT (Informasi Gerakan Internal Anggota Terpadu), a web-based information system designed to transform battalion picket management into an integrated digital ecosystem. The Prototyping development method was adopted to build the system iteratively and responsively to user needs, while Blackbox Testing was used to validate system reliability. The system incorporates Role-Based Access Control (RBAC) to manage access for three user types: Administrator, Organik/Atasan (supervisor), and Kadet (picket officer). A key security feature is a two-factor authentication (2FA) mechanism via Telegram API. Results indicate that INFO GIAT significantly improves the efficiency of picket administration, automates personnel strength recapitulation, and provides a real-time monitoring dashboard for leadership, while minimizing human error and ensuring data transparency and accountability.